Serum microRNA-196 and microRNA-200 in pancreatic ductal adenocarcinoma of patients with diabetes mellitus - Škrha, Pavel; Hořínek, Aleš; Pazourková, Eva; Hajer, Jan; Frič, Přemysl; Škrha, Jan; Anděl, Michal (Pancreatology, 2016)
BACKGROUND/OBJECTIVES: Our aim was to compare expressions of 6 microRNAs (miRNAs) in patients with pancreatic ductal adenocarcinoma (PAC) and non-cancer patients, moreover according to the presence or absence of diabetes mellitus. METHODS: Expressions of miRNA-192, -196, -200, -21, -30 and -423 were measured in 77 patients with PAC and 64 non-cancer patients (34 patients with type 2 DM and 30 control persons). 60 patients with PAC (78%) had DM or prediabetes and it was of new-onset (less than 2 years before the cancer diagnosis) in 44 out of them. RESULTS: The expressions of all microRNAs were 1.4-3.7 times higher (significantly) in the PAC group compared to non-cancer patients. No difference was found between PAC diabetic and PAC non-diabetic patients. MicroRNA-200 was significantly higher in PAC patients with significant body weight loss against those without weight loss. Adding miRNA-196 and -200 to the current marker CA 19-9 improved the discriminative ability of the test (compared to CA 19-9 alone). CONCLUSION: MicroRNA-196 and -200 could be used as additional markers in PAC diagnosis.
Keywords: duktální karcinom slinivky břišní; diabetes mellitus; Diabetes Mellitus; Male; Diabetes Complications; MicroRNAs; prediabetes; CA 19-9; Pancreatic cancer; glykovaný hemoglobin; mikro RNA; Weight Loss; krevní glukóza; Carcinoma, Pancreatic Ductal; Aged; mužské pohlaví; senioři; komplikace diabetu; antigen CA-19-9; Pancreatic Neoplasms; senioři nad 80 let; lidé; ženské pohlaví; Glycated Hemoglobin; Humans; Biomarker; nádory slinivky břišní; Aged, 80 and over; Prediabetic State; Glycated Hemoglobin A; hmotnostní úbytek; miRNA; Female; Blood Glucose; lidé středního věku; Middle Aged; CA-19-9 Antigen